Pengaruh Kompensasi dan Lingkungan Kerja Terhadap Kinerja Pegawai di Badan Perencanaan dan Pembangunan Daerah (BAPPEDA) Kabupaten Tangerang - Prasetyo, Bagas Adi; Suryani, Desy; Purnomo, Martinus Wahyu (CV Warnak Johanna Nusantara, 2026)
Employee performance is a crucial factor in achieving organizational goals, including at the Regional Development Planning Agency (BAPPEDA) of Tangerang Regency. The observed phenomena indicate delays in document completion, low motivation, and a lack of interdepartmental collaboration. These conditions suggest that compensation and the work environment may influence employee performance. This study aims to analyze the effect of compensation and work environment on employee performance at BAPPEDA Tangerang Regency. The research employed a quantitative approach with a survey method by distributing questionnaires to 52 respondents. Data were analyzed using multiple linear regression with the assistance of SPSS version 26. The results show that compensation has a significant effect on employee performance, with a t-value of 4.560 > t-table 1.676 and a significance level of 0.000 < 0.05. The work environment also has a significant effect, with a t-value of 3.588 > t-table 1.676 and a significance level of 0.001 < 0.05. Simultaneously, compensation and work environment significantly affect employee performance, with an F-value of 104.303 > F-table 3.187 and a significance level of 0.000 < 0.05. The coefficient of determination (R²) of 0.802 indicates that 80.2% of the variation in performance is explained by these two variables.